Examining the impact of COVID-19 on entrepreneurial intention through a stimulus-organism-response perspective - Gentjan Çera; Margarita Ndoka; Ines Dika; Edmond Çera (Administrative Sciences, 2022)
Among scholars, there is an interest in understanding how entrepreneurial behavior is influenced by the consequences of crises. The COVID-19 pandemic may negatively or positively affect individuals' behavior, including entrepreneurial intention. Thus, this paper seeks to study whether or not the economic shock caused by the pandemic reinforces the intention to start a business. The research was administered at the individual level by distributing a structured survey. The hypotheses were developed based on a unique conceptual framework integrating the planned behavior theory and a stimulus-organism-response perspective. The relationships were tested using the structural equation modeling method with an original dataset of more than 800 respondents from three post-communist transition countries. The results indicate that the COVID-19 pandemic, seen as an opportunity, positively influences both the antecedents of entrepreneurial intention and individuals' intention to start a business. The message that these findings convey is that, even in crises, there are opportunities from which one can benefit, including the individual's propensity to engage in startup activities. By examining the impact of the COVID-19 crisis on entrepreneurial behavior, educational institutions and policymakers can design effective policies to foster entrepreneurship and reduce unemployment, particularly among the youth.
Keywords: 350; Albania; COVID-19; entrepreneurial intention; Kosovo; North Macedonia; PLS-SEM; theory of planned behavior